2019
DOI: 10.1038/s41467-019-08289-9
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule sequencing detection of N6-methyladenine in microbial reference materials

Abstract: The DNA base modification N6-methyladenine (m6A) is involved in many pathways related to the survival of bacteria and their interactions with hosts. Nanopore sequencing offers a new, portable method to detect base modifications. Here, we show that a neural network can improve m6A detection at trained sequence contexts compared to previously published methods using deviations between measured and expected current values as each adenine travels through a pore. The model, implemented as the mCaller software packa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
140
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(145 citation statements)
references
References 61 publications
3
140
2
Order By: Relevance
“…In addition, this approach provides insight into the diversity of additional HCoV-229E sg RNAs, probably including DI-RNAs. Further, we aim to assess whether RNA modifications can be called directly from the raw nanopore signal of viral molecules without prior in vitro treatment, as has been shown for DNA (Stoiber et al 2016;McIntyre et al 2019).…”
mentioning
confidence: 99%
“…In addition, this approach provides insight into the diversity of additional HCoV-229E sg RNAs, probably including DI-RNAs. Further, we aim to assess whether RNA modifications can be called directly from the raw nanopore signal of viral molecules without prior in vitro treatment, as has been shown for DNA (Stoiber et al 2016;McIntyre et al 2019).…”
mentioning
confidence: 99%
“…They showed that the detection of m5C was easier than that of m6A, contrary to the situation in SMRT sequencing. mCaller can use the four machine learning classifiers (neural network, random forest, logistic regression, and naive Bayes classifiers) to detect m6A on DNA [59]. Mclntyre et al showed that the predictor using the neural network was the most accurate.…”
Section: Tools For Modified Base Detectionmentioning
confidence: 99%
“…Over 40 verified types of covalent nucleotide modifications have been described, of which 5-methylcytosine (5mC) and N6-methyladenine (m 6 A) are the most studied (Sood et al , 2019) . The long read sequencing platforms from Oxford Nanopore Technologies (ONT) enable genome-wide direct observation of modified nucleotides by assessing deviating current signals, for which multiple tools have been developed (McIntyre et al , 2019;Liu, Fang, et al , 2019;Liu, Georgieva, et al , 2019;Rand et al , 2017;Stoiber et al , 2016;Simpson et al , 2017) , but a comprehensive evaluation of their performance is lacking. To the best of our knowledge, no flexible genome browser visualization method is available for this type of data.…”
Section: Introductionmentioning
confidence: 99%